MiR199b Suppresses Expression of Hypoxia-Inducible Factor 1α (HIF-1α) in Prostate Cancer Cells - Hao Zeng (International Journal of Molecular Sciences, 2013)
MicroRNAs (miRNAs) are a class of small noncoding RNAs that post-transcriptionally repress expression of target genes via imperfect base-pairing with the 3'-untranslated region (3'-UTR). The transcription factor hypoxia-inducible factor-1α (HIF-1α) plays important roles in physiology and pathology. Constitutive over-expression of HIF-1α is observed in many types of cancers including prostate carcinoma, but the mechanisms underlying this event remain largely unknown. Here we investigated the expression of miR199b and HIF-1α in normal prostate tissue, prostate cancer tissues and prostate carcinoma (PCa) cell lines LNCaP, PC-3 and DU145.We found that miR-199b expression level was decreased in prostate cancer while HIF-1α was significantly over-expressed. Furthermore, we postulated the posttranscriptional regulation of HIF-1α by miR199b through bioinformatics analysis, and herein we experimentally demonstrated that miR199b negatively regulated HIF-1α by targeting its 3'-untranslated region. Artificial over-expression of miR199b by using adenoviral vectors in prostate cancer PC-3 and DU145 cells significantly down-regulated HIF-1α, together with reduced cell growth and increased cell death.